Enhanced ethene to propene ratio over Zn-modified SAPO-34 zeolites in methanol-to-olefin reaction. Issue 9 (5th April 2019) - Huang, Huiwen; Wang, Haoren; Zhu, Hui; Zhang, Shanhe; Zhang, Qiang; Li, Chunyi
Abstract : The enrichment of incorporated Zn-related species and the accommodation of facilitated aromatics impose increased diffusion restriction for bulky hydrocarbons, thus contributing to significant improvements in ethene selectivity and ethene to propene ratio over Zn modified SAPO-34 zeolites. Abstract : A series of Zn-modified SAPO-34 zeolites were prepared by the impregnation method and the effect of Zn modification on the catalytic performance of SAPO-34 zeolite in the methanol-to-olefin (MTO) reaction was comprehensively investigated. The physicochemical properties of the parent and Zn-modified SAPO-34 zeolites were characterized by XRD, SEM, N2 adsorption–desorption, NH3 -TPD, H2 -TPR, FTIR, UV-vis DRS and TGA. The reaction results show that the ethene selectivity and ethene to propene ratio are significantly improved over Zn-modified SAPO-34 zeolites in the initial period of the MTO reaction, and the optimum catalytic performance is obtained over 2.0Zn/SAPO-34 zeolite with a methanol conversion of 99.1 wt%, an ethene selectivity of 54.6 C-%, a light olefin selectivity of 88.9 C-% and an ethene to propene ratio of 1.9. Based on the characterization and reaction results, the enhanced ethene selectivity and ethene to propene ratio over Zn-modified SAPO-34 zeolites are attributed to the increased diffusion hindrance originating from the incorporated Zn-related species enrichment and the facilitated formation of aromatics.